Comparison of Microbial Community Structure in Kiwifruit Pollens - Kim, Min-Jung (Plant Pathol J, 2018)
Flowers of kiwifruit are morphologically hermaphroditic and survivable binucleate pollen is produced by the male flowers. In this study, we investigated microbial diversity in kiwifruit pollens by analyzing amplicon sequences of 16S rRNA. Four pollen samples were collected: ‘NZ’ was imported from New Zealand, ‘CN’ from China in year of 2014, respectively. ‘KR13’ and ‘KR14’ were collected in 2013′ and 2014′ in South Korea. Most of the identified bacterial phyla in the four different pollens were Proteobacteria, Actinobacteria and Firmicutes. However, the imported and the domestic pollen samples showed different aspects of microbial community structures. The domestic pollens had more diverse in diversity than the imported samples. Among top 20 OTUs, Pseudomonas spp. was the most dominant specie. Interestingly, a bacterial pathogen of kiwifruit canker, Pseudomonas syringae pv. actinidiae was detected in ‘NZ’ by the specific PCR. This study provides insights microbial distribution and community structure information in kiwifruit pollen.